The Ambivalent Role of Social Aspects in Health Promotion - Paula Stehr; Constanze Rossmann; Tabea Kremer; Hanna Luetke Lanfer (University of Zurich, IKMZ - Department of Communication and Media Research, 2022)
Through various mechanisms such as social comparison, social control, and social support, social networks may impose both positive and negative effects on people's health. The purpose of this brief research report is to highlight the role of social aspects in health promotion in the context of evidence-based communication strategies to promote physical activity among older adults in Germany. Results are based on a two-study formative research project, combining 20 semi-structured interviews with a telephone survey of a representative sample of 1,001 older adults. They show that interpersonal communication is an important source of health information. However, a strong normative influence of the social network may also undermine self-determined motivation to be physically active and therefore decrease activity levels in the long-term. In contrast, feeling related to others and being able to exercise together with other people can facilitate physical activity for older adults, which underlines the ambivalent role of social aspects. Hence, (interpersonal) communication aiming at the promotion of physical activity among older adults should support their perceived autonomy by explaining potential health and social consequences of the behaviour, providing choices, and acknowledging individual barriers and facilitators such as (lack of) sports companions.